STRATEGI PENINGKATAN KUALITAS PELAYANAN PORTAL AKADEMIK MAHASISWA DI UNIVERSITAS RIAU TAHUN 2017 - Mutiara Shinta; Rury Febrina (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2019)
The implementation unit of information and communication technology technical is the department that responsible for servicing the students’ academic portal. UPT-TIK as a public unit had to provide the transparence services for students. The well services might improve the quality of Riau University itself. The formulations of the problem in this research were: (1) How was the UPT-TIK strategy in improving the quality of service for the students’ academic portal in Riau University 2017? (2) What obstacles that faced by the UPT-TIK in improving the quality of service for the students’ academic portal in Riau University?. The purpose of this study (1) To described the strategy that used by UPT-TIK in improving the quality of service for the students’ academic portal in Riau University 2017 (2) To described the obstacles that faced by UPT-TIK while implementing the strategy in improving the quality of service for the students’ academic portal in Riau University. This research was descriptive research by using qualitative approach. The result of this study concluded the strategy that used by UPT-TIK in improving the quality of service for the students’ academic portal in Riau University involved technology strategy, innovation strategy, and operation strategy. However, the implementation of the strategy that carried out by UPT-TIK had not been maximized, there were several obstacles that faced by the UPT-TIK in improving the quality of service for the students’ academic portal in Riau University among them were inadequate human resources, lacked of budget funds obtained from the rector of Riau University, not enough servers, the unsuitable technology with the students’ requirements, lacked of training for each divisions and many features in academic portals that did not contain information. Keywords : Strategy, Academic Portal, Service